The Outcome of Cerumen Removal in the Pediatric Emergency Department. Issue 7 (26th July 2022) - Tavor, Oren; Schnapp, Zeev; Soffer, Gili Palnizky; DeRowe, Ari; Rimon, Ayelet
Abstract : Objective: Cerumen obstructs the visualization of the tympanic membrane (TM) in up to 40% of children, sometimes posing a challenge to rule out the diagnosis of acute otitis media (AOM) as the source of otalgia (for verbal children), irritability, fever, and febrile seizures. We aim to determine the rate at which removing the cerumen from blocking the view of the TM could change the management of these patients in the pediatric emergency department (PED). Methods: We retrospectively investigated all medical records of patients who underwent cerumen removal in the PED at a tertiary children's hospital from 2018 to 2019. We analyzed the effect of the procedure on the subsequent workup during their PED visit. Results: Of 482 children who presented to the PED with otalgia, irritability, fever, and/or febrile seizures and who were referred to an otolaryngologist for subsequent treatment after preliminary evaluation in the PED, 176 were included in the study group after having the cerumen removed from one or both ears. Seventy-three of them were given a diagnosis of AOM, 93 had a normal-appearing TM, and 10 had external otitis. Twenty-one percent of those with AOM and 46% of those with a normal TM ( P = 0.008) had blood drawn as part of their workup in their PED visit. The rate of chest x-rays was also significantly less for the AOM group (16% vs 30%, P = 0.03), and they also underwent fewer urine tests ( P = NS). Conclusion: Cerumen removal changes the management of children in the PED who present with a possible diagnosis of an ear infection. Cerumen removal could avoid unnecessary laboratory and imaging studies, which could save time, costs, and suffering.